The effectiveness of systemic-constructivist couple therapy (scct) on marital satisfaction and intimacy in older women-younger men marriages - mojtaba noorani; Rezvanossadat Jazayeri; Maryam Fatehizadeh (مجله علوم روانشناختی, 2021)
Background: Many studies have been conducted on marital satisfaction and intimacy of couples, but research on the effectiveness of systemic-constructivist couple therapy on intimacy and marital satisfaction, especially in Older women-younger men couples, has been neglected. Aims: The aim of this study was to evaluate the effectiveness of Systemic-Constructivist Couple Therapy (SCCT) on Marital Satisfaction and Intimacy in Older women-younger men marriages. Methods: This was a quasi-experimental study with a pre-test, post-test design, and follow-up with an experimental group and a control group. The population of this study consisted of all couples in older women-younger men marriages in Shiraz in 2019. Using the convenience sampling method, 30 couples were selected and randomly divided into experimental and control groups. In the pre-test stage, the short form of Enrich Marital Satisfaction Questionnaire (olson, 1998) and the couple intimacy (oulia, 2006) were given to both groups and then the systemic-constructivist couple therapy approach in 9 sessions per week Two hours, were performed for the experimental group. In order to analyze the data, repeated measures analysis of variance was used. Results: The results of data analysis showed that systemic-constructive couple therapy on marital satisfaction and dimensions of emotional, intellectual, psychological, socio-recreational, communication, and general intimacy, had a significant effect (P> 0.05), while these interventions did not have a significant effect on physical, spiritual, and sexual intimacy. Conclusion: Conclusions: From the obtained results, it can be concluded that systemic-constructivist couple therapy can be used to improve marital satisfaction and intimacy of couples.